Effect Of Concrete Grade On Carbonation Intrusion: A Systematic Review - Mohamed Ariff, Nur Farah Wahidah; Juki, Mohd Irwan; Abdullah Faisal Alshalif (Recent Trends in Civil Engineering and Built Environment, 2021)
Concrete is one of the most widely materials used in building for its behavior, strength in the concrete as a secure, strong, and simple object. It is designed to ensure reliable and high-quality rapid-track construction. Water to cement ratio plays a crucial role, affecting various attributes, such as strength, workability and durability of the concrete. Carbonation is one of the many important factors that decide their service life in the construction of concrete structures. The carbonation effect due to carbonation in reinforced concrete is the loss of steel passivity, that in turn results to corrosion along with spalling and cracking of concrete, but it is more durable in plain concrete since it makes the concrete completely denser, increases sulphate and alkali aggregate resistance and decrease the porosity. Suitable test procedures for the measurement of porosity and compressive strength chosen from a review of the available techniques that often been used by researchers. In this study, the used of systematic literature review had evaluate the objective of this study. Boolean operator played an important role in search engine database. The outcomes of this study will demonstrate the effect of the concrete grade on the intrusion of carbonation, which can lead to increases the compressive and reduce the porosity of concrete.